Structure and Magnetic-field Induced Effects in Mn-Ni(Fe)-Sn Metamagnetic Shape Memory Alloys. (2015) - Sasmaz, M.; Chernenko, V.A.; Martinez, E.; Lázpita, P.; Barandiarán, J.M.; Gutiérrez, J.; Aydogdu, Y.
Abstract: Martensitic structures, transformation behavior and some magnetic properties of a new series of Mn49 Ni42-x Fex Sn9 (x = 0 – 4 at.%) metamagnetic shape memory alloys have been studied as a function of Fe content and magnetic field. Fe doping decreased sharply the martensitic transformation temperatures. The XRD patterns showed different phases including orthorhombic structure, the L21 cubic phase and the fcc γ-phase at room temperature depending on Fe content. The magnetization curves, M-H, exhibited obvious metamagnetic transitions.